2015
DOI: 10.1007/s10195-015-0377-4
|View full text |Cite
|
Sign up to set email alerts
|

Congenital idiopathic talipes equinovarus before and after walking age: observations and strategy of treatment from a series of 88 cases

Abstract: BackgroundWe reviewed a series of newborns, toddlers and ambulating children affected by idiopathic congenital talipes equinovarus (clubfoot). Taking into account the time of diagnosis, stiffness of the deformity and walking age, nonsurgical or surgical treatment was considered. This study reports clinical outcomes, early complications and relapse at mid-term follow-up.Materials and methodsFifty-two clubfeet were diagnosed at birth, 12 in non-ambulating children aged between 4 and 12 months and 24 in ambulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…However, the authors emphasized the advantages of MRI in complex CTEV, while in cases of isolated CTEV its utility is questionable. Servaes et al present MRI as a tool capable of accurately detecting clubfoot; despite this, MRI should not be used as a preferential prenatal diagnostic procedure for clubfoot since its effects on the fetus are still unclear [ 6 ]. A comparison between the accuracy of ultrasound and MRI is not possible since the data for the latter technique is not specified in the reviewed studies, which adds to the unclear reliability of this methodology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors emphasized the advantages of MRI in complex CTEV, while in cases of isolated CTEV its utility is questionable. Servaes et al present MRI as a tool capable of accurately detecting clubfoot; despite this, MRI should not be used as a preferential prenatal diagnostic procedure for clubfoot since its effects on the fetus are still unclear [ 6 ]. A comparison between the accuracy of ultrasound and MRI is not possible since the data for the latter technique is not specified in the reviewed studies, which adds to the unclear reliability of this methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the US, MRI is not adopted as a screening method due to unclear effects on the developing fetus [ 6 ] and the high cost of the procedure. Some authors reported that in the case of positive US, MRI does not advance findings.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, Faldini et al (32) published their study on 88 clubfeet treated with Ponseti method, considering the difference in starting the treatment before or during walking-age; in their experience, newborns and non-walking children may be more successfully treated with serial casting than walking children, underlining the importance of starting treatment at birth to achieve good outcomes. However, even that nonsurgical treatment is less effective during and after walking age, re-casting with the Ponseti technique remain a valuable mean to limit the invasiveness of surgical procedures in older children.…”
Section: Ponseti Methodsmentioning
confidence: 99%
“…Idiopathic clubfoot is characterized by an alteration of the morphology of the foot and its position with the leg, so the foot cannot physiologically move on the ground. For these reasons, the treatment should aim to correct the four components of the deformity in such a way as to restore as much as possible of the anatomic shape and function of the foot to allow plantigrade stance and proper gait (2) . Timely Ponseti treatment starts with gentle manipulative and plaster cast treatment, gives excellent and very good results in 92-95% of cases and the only surgical intervention in this primary stage is percutaneous tendon Achilles tenotomy.…”
Section: Introductionmentioning
confidence: 99%